Colonic permeability is increased in non-cirrhotic patients with nonalcoholic fatty liver disease. Issue 5 (May 2023) - De Munck, Toon J.I.; Verhaegh, Pauline; Spooren, Corinne; Mujagic, Zlatan; Wienhold, Tobias; Jonkers, Daisy; Masclee, Ad A.M.; Koek, Ger H.; Verbeek, Jef
Abstract: Background and aim: Intestinal permeability (IP) plays an important role in the pathophysiology of nonalcoholic fatty liver disease (NAFLD). We assessed site-specific (gastroduodenum, small intestine, colon and whole gut) IP in NAFLD patients and healthy controls (HC) and its association with the degree of hepatic steatosis, hepatic fibrosis and dietary composition in these NAFLD patients. Methods: In vivo site-specific IP was analysed with a validated multi-sugar test in NAFLD patients and HC. Furthermore, in NAFLD patients, hepatic steatosis (chemical shift MRI), hepatic fibrosis (transient elastography) and dietary composition (food frequency questionnaire) were assessed. Results: Fifty-two NAFLD patients and forty-six HC were included in this study. Small intestinal ( P <0.001), colonic ( P  = 0.004) and whole gut ( P <0.001) permeability were increased in NAFLD patients compared to HC. Furthermore, colonic permeability ( P  = 0.029) was significantly higher in NAFLD patients with clinically significant fibrosis compared to those without. Colonic permeability remained positively associated with the presence of clinically significant fibrosis ( P  = 0.017) after adjustment for age, sex and BMI. Conclusion: Colonic permeability is increased in at least a subset of NAFLD patients compared to HC and is independently associated with clinically significant NAFLD fibrosis.